Myoepithelial carcinoma of the nasopharynx: Rare case report with clinicopathologic and immunohistochemical features review of literature. Issue 6 (23rd March 2018) - Chen, Linyan; Fu, Yiyun; Wang, Haiyang; Yang, Fuyao; Liu, Jun; Xia, Fan; Ma, Xuelei
Abstract: Background: Myoepithelial carcinoma is a rare salivary carcinoma, which most often arises from the major salivary glands. Only a few cases of myoepithelial carcinoma of the nasopharynx have been reported, thus, the treatment guideline and prognosis remain undefined. Methods: We reported a case of nasopharyngeal myoepithelial carcinoma in a 31‐year‐old man. The tumor cells showed specific cell types and arrangements histologically, which were immunoreactive with myoepithelial markers. The patient received surgical excision with transpalatal approach. A literature review of previous cases was also presented. Results: The patient reflected residual tumor 4 weeks later. After concurrent chemoradiotherapy (CRT), the tumor reduced and remained stable without signs of progression. Conclusion: The nasopharyngeal mass with spindled, plasmacytoid, epithelioid, and clear cell types, was suggested to raise the suspicion of myoepithelial carcinoma in order to diagnose and treat early. The wide surgical excision followed by optimal adjuvant therapy might offer a mode of treatment with better survival results.